Introduction to mechatronics and measurement systems - Histand, Michael B. (McGraw-Hill series in mechanical engineering., 1999)
"Introduction to Mechatronics and Measurement Systems provides an accessible overview of the evolving field of mechatronics. Michael B. Histand and David G. Alciatore have taken careful steps to present measurement system and electronic engineering fundamentals, which are instrumental in understanding mechatronic systems, to your students. This new text has been class-tested over several years to ensure complete accuracy. In addition to analysis techniques, design considerations are presented throughout the text. The text's numerous illustrations, examples, and problems provide an opportunity to see and apply mechatronics to actual problems encountered in engineering practice."--Jacket.